Providing Career Understanding Services for Junior High School Students at SMP Negeri 11 Kupang City - Alamat, Yosef Mario Rama; Erlinda, Maria (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2026)
Understanding students' career aspirations in junior high school (SMP) 11 kota Kupang is a crucial topic in the context of education and career development. A strong grasp of career choices can aid students in making informed decisions regarding their future education, training, and employment options, significantly impacting their developmental trajectory. A robust understanding of career pathways enhances students' learning motivation, reduces confusion in selecting educational and vocational paths, and assists in formulating realistic, future-oriented career plans.